2014
DOI: 10.1007/s10086-014-1449-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface deterioration of wood plastic composites under outdoor exposure

Abstract: Outdoor exposure tests of wood plastic composites (WPCs) were conducted at seven sites in Japan. The tests examined the process of chalking on the surface of the WPCs and the weather factors affecting chalking. Observations using a scanning electron microscope and a polarization optical microscope (POM), analyses of Fourier transform infrared spectroscopy, as well as differential scanning calorimetry showed that the deterioration of both wood and polyolefin elements occurs on the surface of WPCs. The POM obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Pine/polyethylene composites with 70% particle content showed considerably higher weight loss than composites made of 50% particle content. Moreover, the results of this study also complied with the results reported by Verhey et al [23] and Ebe and Sekino [13], because WPCs with higher particle contents are more susceptible to natural decay. Moreover, Kartal et al [24] described similar results that the composites having large particles showed a lower weight loss than the smaller particle sized specimens.…”
Section: Decay Resistancesupporting
confidence: 92%
See 1 more Smart Citation
“…Pine/polyethylene composites with 70% particle content showed considerably higher weight loss than composites made of 50% particle content. Moreover, the results of this study also complied with the results reported by Verhey et al [23] and Ebe and Sekino [13], because WPCs with higher particle contents are more susceptible to natural decay. Moreover, Kartal et al [24] described similar results that the composites having large particles showed a lower weight loss than the smaller particle sized specimens.…”
Section: Decay Resistancesupporting
confidence: 92%
“…In an earlier research, Chen et al [6] reported that the large size wood particles increased the bending strength and decreased the density of composites. In the meantime, natural decay resistance or durability is another important issue for the WPCs performance and recent concerns about it is increasing [13], because wood particles or fibers are biodegradable [13] and hygroscopic [2] in nature that exposed to extreme conditions. However, Rahman et al [3] did not report the decay resistance of the WPCs in the earlier research.…”
Section: Introductionmentioning
confidence: 99%
“…The methods described in the specification [16][17][18][19] were followed. Specifically, a Fourier transform infrared spectrometer (FTIR, Thermo Scientific Nicolet-6700) was used to measure the infrared absorption spectrum of the postexposure PE-RS sample films (thickness 0.2 mm) in the range from 2200 cm −1 to 1600 cm −1 on transmission mode at a typical average of 24 scans, and the CI was calculated from the absorbances at around 1715 cm …”
Section: Carbonyl Index (Ci)mentioning
confidence: 99%
“…Many data of weathering test for adhesives and other outdoor applications were published [13][14][15]. Thus, the objective of this joint study was to perform accelerated weathering testing and outdoor exposure testing of a polyethylene reference sample (PE-RS) [16][17][18][19] and six types of polypropylene (PP) at public research organizations under the Polymer Subcommittee in the Industrial Technology Cooperative Promotion Committee (Japan) to obtain findings regarding the reproducibility and acceleration of the accelerated weathering testing and the correlation between the accelerated weathering testing and outdoor exposure testing as indicated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Pigments, light stabilizers, and UVAs have been investigated to improve the color stability of WPCs. 16 18…”
Section: Introductionmentioning
confidence: 99%